Early postoperative patient-reported outcomes in thoracoscopic segmentectomy: a comparative study of non-intubated anesthesia versus intubated general anesthesia - Guan, He; Bi, Jinchao; Zheng, Wantong; Zhang, Yahao; Han, Zhijun; Wei, Li; Li, Jiwei (Frontiers in Oncology, 2025)
IntroductionSegmentectomy under non-intubated anesthesia (NIA) has demonstrated comparable conventional clinical outcomes to segmentectomy performed under intubated general anesthesia (IGA). However, differences in early patient-reported outcomes (PROs) between the two anesthetic approaches remain unclear. This study aimed to evaluate symptom burden and functional status from the patient’s perspective under different anesthesia modalities.MethodsPatients who underwent segmentectomy via either IGA or NIA were included. Perioperative symptom severity and functional status were assessed using the PSA-lung scale. PROs data were collected at various perioperative time points, and comparisons between groups were analyzed using a linear mixed-effects model.ResultsAmong the 380 enrolled patients, 160 underwent segmentectomy under NIA, and 220 under IGA. After propensity score matching (PSM), baseline characteristics were comparable between groups. On postoperative day 7, patients in the NIA group reported significantly milder symptoms of pain (P<0.001), cough (P<0.001), dyspnea (P=0.011), and drowsiness (P<0.001) compared to those in the IGA group. Additionally, the NIA group experienced less functional interference in walking (P<0.001) and general function (P<0.001). Within one month postoperatively, patients in the IGA group reported more severe cough (P<0.001) and anxiety (P<0.001) than those in the NIA group. There were no significant differences in short-term clinical outcomes between the two groups, although the NIA group had a longer operative time (P<0.001) but a shorter postoperative hospital stay (P<0.001).DiscussionPROs are essential indicators of postoperative recovery after segmentectomy. Compared to intubated anesthesia, non-intubated anesthesia is associated with fewer severe early symptoms, lower functional burden, and shorter hospitalization following segmentectomy.